(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): The present study designed to explore topics related to Tuberculosis, such as new smear positive cases, causes, treatment and new pulmonary positive cases in Baghdad City, Iraq for 2012-2016. Methods: A descriptive “retrospective” design was performed throughout the present study from the period of November 12th 2017 to February 13th 2018. All registered tuberculosis patients in Baghdad, Iraq for the period of 2012-2016. An instrument was constructed for the purpose of the study. Data were collected from the health records at the National Tuberculosis Center, State TB center, and district TB center for the period of 2012 to 2016 with the use of the study instrument. Data were analyzed through the application of descriptive statistical data analysis approach of frequency, percent, incidence rate and ratio. Results: The study findings depicted that most of the new smear positive cases are accounted for the age group of (15-24) year old during the years of 2012-2016. Causes of Tuberculosis in the rural area were accounted for poverty (39.95%), smoking (22.39%), untreated cases (12.4%), alcoholism (11.32%), malnutrition (10.30%) and overcrowded (3.57%) respectively, and accounted for alcoholism (27.77%), overcrowded (27.16%), malnutrition (24.69%), smoking (11.93%), poverty (7.62%) and untreated cases of Tuberculosis (0.80%) respectively in the urban area. Conclusion: The study concluded that Most of the new smear positive cases are accounted for the age group of (15-24) year old during the years of 2012-2016. Patients, in 2014, had benefited out of the Tuberculosis Program more than others based on the success rate.